2017
DOI: 10.1038/s41598-017-04242-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of city size and urban form in the surface urban heat island

Abstract: Urban climate is determined by a variety of factors, whose knowledge can help to attenuate heat stress in the context of ongoing urbanization and climate change. We study the influence of city size and urban form on the Urban Heat Island (UHI) phenomenon in Europe and find a complex interplay between UHI intensity and city size, fractality, and anisometry. Due to correlations among these urban factors, interactions in the multi-linear regression need to be taken into account. We find that among the largest 5,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
213
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(237 citation statements)
references
References 46 publications
12
213
1
11
Order By: Relevance
“…Third, although this paper is primarily a theoretical study, the results can still shed some insights into answering practical questions. For example, remote sensing studies have found that the difference between urban and rural surface temperatures strongly increases as x increases, where x is the distance from the edge of the city, until it reaches the center of the city (Zhou et al, ; ). Based on the ADE model results, this cannot be simply attributed to the imperviousness of the city as the reduction of β would cause the opposite behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Third, although this paper is primarily a theoretical study, the results can still shed some insights into answering practical questions. For example, remote sensing studies have found that the difference between urban and rural surface temperatures strongly increases as x increases, where x is the distance from the edge of the city, until it reaches the center of the city (Zhou et al, ; ). Based on the ADE model results, this cannot be simply attributed to the imperviousness of the city as the reduction of β would cause the opposite behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of higher urban surface temperature is technically referred to as surface urban heat islands (SUHIs) [9,10]. This phenomenon is generally observed in cities, and its intensity depends on several factors including size, population, location, socio-economic activities, urban planning, and land use policies of the area under consideration [7,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the analysis was of change in (dry bulb) temperatures alone, taking no account humidity, or evidence on the precise form of the distribution of daily temperatures. Moreover, the analyses did not attempt to incorporate the urban heat island (UHI) effect-the name given to the occurrence of higher outdoor temperatures in metropolitan areas compared with those of the surrounding countryside caused by the thermal properties (heat absorption, capacity, conductance, and albedo) of the surfaces and materials found in urban landscapes, the reduced evapotranspiration from reduced natural vegetation, and the waste heat production from anthropogenic activities [28][29][30]. The UHI effect may add to the more general effect of increasing temperatures, especially in larger cities, though the implications for personal exposure and health are more complex [31,32] and surface temperature effects may in part be offset by overshadowing by high rise buildings in urban centres [33].…”
Section: Discussionmentioning
confidence: 99%